Immune deficit in recurrent pyogenic cholangitis - Nor, Norazmi Mohd; Khan, Taufeeq T.F. (1999)
As the name suggests, patients with recurrent pyogenic cholangitis (RPC) are prone to repeated episodes of cholangitis with systemic sepsis. The mechanism and pathogenesis of sepsis in these patients is not well understood, although some animal studies have suggest a functional defect in the immune system. To determine whether an immunological deficit may account for RPC, we conducted a pilot study to assess the immune status of these patients and compared it to a control group. Using two-colour flow cytometry, we found that the absolute number of various lymphocytes subpopulations, namely total T cells (CD3+), CD4+ T cells, total B cells (CD19t) and natural killer (NK) cells (CD16+56+) seemed to be depressed in patients with RPC as compared to the control group. In addition we observed that these patients had higher levels of CDS+ cells expressing the CD38 activation marker. Although based on a small sample size, these findings suggest that immune depression may be an important feature of RPC.